Education for Sustainability through Gamification - Dudok, Fanni; Pigniczki-Kovács, Eszter (Acta Cultura et Paedagogicae, 2024)
The study explores the intersection of sustainability education and gamification, focusing on the application of the "Green Walker" board game in educational settings. It addresses the role of educational institutions in sustainability education, methodological approaches to sustainability education, and the significance and efficacy of gamification in enhancing learning motivation and cognitive skills. The empirical research concentrates on the outcomes of implementing the "Zöld járőr" game in schools, examining its impact on students' sustainability consciousness and attitudes. The findings indicate that gamified educational tools significantly contribute to reinforcing sustainability knowledge and fostering environmentally responsible behaviours among students. The research underscores the importance of integrating sustainability education with gamification in education and highlights the potential benefits of game-based learning for developing sustainability competencies.